An investigation of the consumer socialization process of rural migrant workers in China. - Wang, Jian Feng. (2008)
This research investigates the consumer behavior of rural migrants within the People’s Republic of China (PRC) who move from inner-province villages to larger cities or newly developed industrial centers for better opportunities and pays. These consumers arrive in the cities as almost blank slates, with few prior encounter with consumer products.